2011
DOI: 10.1159/000323284
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Hazard in the Aetiology of Somatic and Germ Cell Aneuploidy

Abstract: Sources of environmental exposures to potentially aneugenic agents are many and include occupational and therapeutic exposures, and exposures associated with lifestyle habits. In this present study, some of these agents and exposure scenarios are discussed that involve potentially large population targets and/or seem to affect chromosome segregation by previously unsuspected mechanisms: metals, possibly acting by epigenetic mechanisms; nano-sized particles that might directly interact with subcellular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 275 publications
0
9
0
Order By: Relevance
“…The designation of specific environmental exposures as aneugens in humans has been problematic, with both supportive and non-supportive data being reported for a variety of toxins/lifestyle exposures [ 92 ]. In studies that were performed using mice, Hunt et al [ 93 ] clearly showed an increase in aneuploidy frequencies in response to Bisphenol A (BPA) exposure.…”
Section: Constitutional Autosomal Aneuploidymentioning
confidence: 99%
See 1 more Smart Citation
“…The designation of specific environmental exposures as aneugens in humans has been problematic, with both supportive and non-supportive data being reported for a variety of toxins/lifestyle exposures [ 92 ]. In studies that were performed using mice, Hunt et al [ 93 ] clearly showed an increase in aneuploidy frequencies in response to Bisphenol A (BPA) exposure.…”
Section: Constitutional Autosomal Aneuploidymentioning
confidence: 99%
“…In addition to chromosome-specific variation in aneuploidy frequencies, individual-specific variation in acquired aneuploidy and micronuclei frequencies has been reported [ 35,109,126,128,130,149,150 ], with both genetic (65% of variance) and environmental (35% of variance) factors being shown to influence these frequencies [ 92,119,131 ] (Figure 5). Environmental exposures that have been shown to increase the frequency of micronuclei include, but are not limited to, diet (especially folate deficiency) [ 131,151-153 ], hormone levels [ 131,154 ], tobacco, alcohol and occupational hazards [ 119,131 ].…”
Section: Acquired Autosomal Aneuploidy In Healthy Individualsmentioning
confidence: 99%
“…One potential factor involved in the reduction of oocyte quality over time is the accumulation of toxic elements from the environment that could damage the meiotic machinery. 1820 The cellular components of the oocyte and the somatic compartment are exposed to toxic influences that depend on the chronological age of the oocyte, lifestyle, and environment. Along with the intrinsic aging process of the oocyte, diminished oocyte quality could result from damage by reactive oxygen species from metabolism.…”
mentioning
confidence: 99%
“…Our investigations in MIC treated IMR-90, HEK-293 and FHC cells presented the overexpression of centrosomal protein pericentrin levels suggestive of an abnormal centrosome functioning, thereby generating supernumerary centrioles and improper segregation of chromosomes during cell division. Moreover, surpassing of the cellular capacity to aptly manage spindle assembly checkpoints results in chromosome mis-segregation with subsequent "gain of chromosomal-instable phenotype" and leads to profound karyotype instability [56]. Environmental mutagenic agents, in this regard, can predispose and produce heritable chromosomal aberrations leading to unbalanced complements of chromosomes with varying degrees of severity.…”
Section: Cell Cycle Checkpointsmentioning
confidence: 99%